Key indicators for Asia and the Pacific 2023 - Asian Development Bank (Mandaluyong City, Metro Manila Asian Development Bank, 2023)
Part I. Sustainable Development Goals: The SDGs comprise 169 targets across 17 goals to be achieved by 2030. This section includes data tables and brief analyses of trends for select SDG indicators for which data are available. The indicators are presented according to the United Nations SDG global indicator framework - - Part II. Region at a Glance: The regional tables are grouped into eight themes: People; Economy and Output; Money, Finance, and Prices; Globalization; Transport and Communications; Energy and Electricity; Environment; and Government and Governance. This chapter also presents analysis of key trends for select indicators, highlighting important recent developments in Asia and the Pacific - - Part III. Global Value Chains: This chapter highlights the polarity effects of inflation and exchange rate changes on participation in global value chains by economies in Asia and the Pacific. Real GVC participation is introduced as an indicator to supplement nominal measures of GVC participation. It measures participation in value chains involving multiple cross-border transaction of inputs used in different stages of production expressed in constant (base year 2010) prices - - Part IV. Stories Behind the Data: Using Price Data and Statistics to Track Socioeconomic Development: This chapter highlights the vital role of timely and reliable temporal and spatial price statistics. It presents the crucial role of national statistical systems (NSSs) in compiling policy-essential price indices such as consumer price index, which track price changes over time. The chapter also underscores the significant contributions of the NSSs in the International Comparison Program (ICP) which produces purchasing power parities, which are spatial price indices free from price level differences used to express gross domestic expenditure aggregates using a common currency across economies.
Keywords: Economics; Poverty; Statistics